THE MOBILIZATION OF WATER IN THERMAL REGULATION - PI SUNER, JAIME (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1940)
Describes the egg of A lacustris, of large size (42-6 mm), smooth capsule, large perivitelline space and yolk, which during embryonic development enlarges and changes form; masses of millions of the eggs float in the bays of the Lake of Patzcuaro (Mexi
CIENC MEX
Keywords: MOBILIZATION, WATER, THERMAL REGULATION; MULTIDISCIPLINARIA; INGENIERIA AGRICOLA; RIEGO